Racial disparities in preemptive referral for kidney transplantation in Georgia. Issue 9 (26th August 2018) - Gander, Jennifer C.; Zhang, Xingyu; Plantinga, Laura; Paul, Sudeshna; Basu, Mohua; Pastan, Stephen O.; Gibney, Eric; Hartmann, Erica; Mulloy, Laura; Zayas, Carlos; Patzer, Rachel E.
Abstract: Background: Racial disparities persist in access to kidney transplantation. Racial differences in preemptive referral, or referral prior to dialysis start, may explain this discrepancy. Methods: Patient‐level data on kidney transplant referrals (2005‐2012) from all Georgia transplant centers were linked to the United States Renal Data System to examine racial disparities in preemptive referral, waitlisting, and living donor transplant. Adjusted logistic regression and Cox proportional hazard models determined the associations between race (African American vs white) and preemptive referral, and placement on the waitlist and receipt of a living donor kidney, respectively. Results: Among 7752 adults referred for transplant evaluation, 20.38% (n = 1580) were preemptively referred. The odds of African Americans being preemptively referred for transplant evaluation were 37% (OR = 0.63; [95% CI: 0.55 0.71]) lower than white patients. Among preemptively referred patients, there was no racial difference (African Americans compared to white patients. HR = 0.96; [95% CI: 0.88, 1.04]) in waitlisting. However, African Americans were 70% less likely than white patients to receive a living donor transplant (HR = 0.30; [95% CI: 0.21, 0.42]). Conclusion: Racial disparities in transplant receipt may be partially explained by disparities in preemptive referral. Interventions to reduce racial disparities in kidney transplant access may need to be targeted earlier in the disease process.